Indonesia-US Trade Barrier: A Study on the Halal Certification of Imported Chicken Leg Quarters - Akim Akim; Arfin Sudirman; Januar Aditya Pratama (Jurnal Hubungan Internasional, 2023)
This study discussed the background of Indonesia's non-tariff trade barrier implementation against imports of chicken legs from the United States (US) through halal certification. As WTO members, the two countries are bound by the rules and agreements of the WTO, one of which is trade liberalization related to the elimination of various kinds of trade barrier including non-tariff trade barrier such as halal certification. The application of halal certification by Indonesia to imports of chicken legs has prevented imported chicken legs from the US from entering the Indonesian market, even though they have a lower price. This study uses a mercantilism approach in the global political economy, namely the theory of non-tariff trade barrier from Thomas Oatley. The method used by the researcher was a qualitative research method with the type of case study and data collection techniques are carried out through literature study and interviews with related informants. This study concludes that there were two considerations behind the implementation of non-tariff trade barrier by Indonesia to the import of chicken legs from the US through halal certification, namely the consideration of a society-centered approach to protect public confidence, protect producers, and domestic livestock workers and considerations that are state-centered in the context of handling the economic crisis in the livestock sector and saving the state's foreign exchange expenditure.